Strategy for Business Development of Yogya Kremes Chicken Restaurant in Tulang Bawang District - M. Pindra; Ni Putu Widhia Rahayu (Formosa Journal of Multidisciplinary Research, 2024)
The smallest number of MSMEs in the Tulang Bawang area is 23 and have not experienced any development compared to other districts/cities in Lampung Province. The aim of the research is to analyze business development strategies using SWOT analysis. The research method used in this research is using a qualitative approach with SWOT analysis. The questionnaire will be distributed online with a total of 44 respondents. The results of the research show that the Yogya Tulang Bawang Kremes Chicken Restaurant is in quadrant 1 (Growth) between Strength and Opportunity.